MELESTARIKAN MINUMAN TRADISIONAL KHAS JAWA TIMUR SEBAGAI POTENSI PENGEMBANGAN WISATA KULINER (CULINARY TOURISM) - Dafila Tanico (Jurnal Pariwisata Pesona, 2016)
East Java has a traditional drink, which can be displayed as an attraction for tourists visiting a region in East Java. Typical drink of East Java in every region has a characteristic different, affecting It is a state of geographic regions, customs, cultural diversity, and so forth. Drinks typical eastern Java including wedang angsle, wedang jaselang, wedang cemue, ice buto ijo, ice gudir, sinom ice, ice pleret typical heritages blitar , Syrup Pokak, jamu Kebonagung, Ice Anaconda Lumajang, Tea shake and others - others. Drinks Beverage can in developed as appeal especially culinary. Culinary tours can be interpreted as a search for a unique culinary experience and always remembered with various types, which often enjoyed in every trip. to develop culinary tourism, especially East Java traditional drinks such as providing the latest innovations to a type of traditional drinks without eliminating the element of distinctiveness of an area. In addition to holding a special festival serves traditional drinks of East Java